Unveiling the Emerging Role of Extracellular Vesicle–Inflammasomes in Hyperoxia-Induced Neonatal Lung and Brain Injury - Karen Young; Merline Benny; Augusto Schmidt; Shu Wu (Cells)
Extremely premature infants are at significant risk for developing bronchopulmonary dysplasia (BPD) and neurodevelopmental impairment (NDI). Although BPD is a predictor of poor neurodevelopmental outcomes, it is currently unknown how BPD contributes to brain injury and long-term NDI in pre-term infants. Extracellular vesicles (EVs) are small, membrane-bound structures released from cells into the surrounding environment. EVs are involved in inter-organ communication in diverse pathological processes. Inflammasomes are large, multiprotein complexes that are part of the innate immune system and are responsible for triggering inflammatory responses and cell death. Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is pivotal in inflammasome assembly and activating inflammatory caspase-1. Activated caspase-1 cleaves gasdermin D (GSDMD) to release a 30 kD N-terminal domain that can form membrane pores, leading to lytic cell death, also known as pyroptosis. Activated caspase-1 can also cleave pro-IL-1β and pro-IL-18 to their active forms, which can be rapidly released through the GSDMD pores to induce inflammation. Recent evidence has emerged that activation of inflammasomes is associated with neonatal lung and brain injury, and inhibition of inflammasomes reduces hyperoxia-induced neonatal lung and brain injury. Additionally, multiple studies have demonstrated that hyperoxia stimulates the release of lung-derived EVs that contain inflammasome cargos. Adoptive transfer of these EVs into the circulation of normal neonatal mice and rats induces brain inflammatory injury. This review focuses on EV–inflammasomes’ roles in mediating lung-to-brain crosstalk via EV-dependent and EV-independent mechanisms critical in BPD, brain injury, and NDI pathogenesis. EV–inflammasomes will be discussed as potential therapeutic targets for neonatal lung and brain injury.